2017
DOI: 10.1016/j.jaging.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Organizational capacities for ‘residential care homes for the elderly’ to provide culturally appropriate end-of-life care for Chinese elders and their families

Abstract: Developing culturally appropriate end-of-life care for Chinese elderly and families is not an endemic challenge for Hong Kong, but that of the Western countries with a noticeable trend of rising Chinese population. The particular development of Hong Kong healthcare system, which is currently the major provider of end-of-life care, makes Hong Kong a fruitful case for understanding the confluence of the West and the East cultures in end-of-life care practices. This study therefore aims at building our best pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In general, healthcare professionals may not have experience in EOL care, causing delay in referrals and moral stress in the discussion. This is consistent with other findings which also reported that despite having medical knowledge, healthcare providers may lack the skills and knowledge to provide palliative care services [ 8 , 13 , 15 , 23 , 24 ]. It echoes with the findings of a study in Hong Kong about the association between staff training in nursing homes and their willingness, competence, and self-care [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…In general, healthcare professionals may not have experience in EOL care, causing delay in referrals and moral stress in the discussion. This is consistent with other findings which also reported that despite having medical knowledge, healthcare providers may lack the skills and knowledge to provide palliative care services [ 8 , 13 , 15 , 23 , 24 ]. It echoes with the findings of a study in Hong Kong about the association between staff training in nursing homes and their willingness, competence, and self-care [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…Traditional Chinese culture, particularly Confucianism, recognizes treating others with dignity as a core concept in thought and moral practice. It fully acknowledges one’s humanity, particularly those with cognitive challenges or functional limitations (Kong et al, 2017). It recognizes human dignity as realized through relationships and interactions between self and others, which echoes the values of PCC and the senses framework (Nolan et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Chinese culture can serve as a premise or facilitator for operationalizing PCC in China, such as the concept of showing respect and treating others with dignity. However, some values and notions in Chinese culture can be barriers to applying PCC, such as the understanding of personhood, maintaining relational or family harmony at the expense of communicating or expressing oneself (Kong et al, 2017). Persons with dementia require a holistic, collaborative, and ongoing understanding from their care partners of their needs and preferred self to maintain meaningful social relationships and achieve a sense of belonging and continuity (McCormack & McCance., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…14,18 One possible explanation for this results is that residential care facilities lack timely communication and coordination between their staff and the hospice care clinicians. 25 In addition, policies and procedures in residential care facilities may hinder or impede coordination of care with other providers such as hospice. 25 Alternatively, residential care facilities may lack the advanced clinical expertise to accurately assess end-of-life trajectories in children with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%